2021
DOI: 10.1111/jfpe.13702
|View full text |Cite
|
Sign up to set email alerts
|

Annealing process improves the physical, functional, thermal, and rheological properties of Andean oca (Oxalis tuberosa) starch

Abstract: The characteristics of a native starch limit its application in the food industry; for this reason, it is important to investigate alternatives for obtaining modified starches with better characteristics and more possibilities of application. Oca (Oxalis tuberosa) starch was subjected to annealing process with a temperature of 42 and 50 C and starch:water ratios of 1:6 and 1:2 during 24 hr. The effects of the annealing process on thermal, structural, and rheological properties were investigated. The annealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Starch granules' dehydration and molecular rearrangement may be responsible for the microstructural changes [21]. Some researchers reported no significant morphological changes in starch, especially in the integrity and starch shape [22], granule size [13], and granules presented [15]. In this study, the effect of annealing on starch morphology was not observed.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Starch granules' dehydration and molecular rearrangement may be responsible for the microstructural changes [21]. Some researchers reported no significant morphological changes in starch, especially in the integrity and starch shape [22], granule size [13], and granules presented [15]. In this study, the effect of annealing on starch morphology was not observed.…”
Section: Resultscontrasting
confidence: 55%
“…In the initial phase of gelatinization, water will be imbibed, which causes swelling of the starch granule size. Puelles-Roman et al [13] reported annealing modified starch granule size enlargement.…”
Section: Glucomannan Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] The higher temperatures are related to a partial gelatinization of starch during annealing. [ 53 ] The results indicate that annealing improves the crystalline quality of starch by agglomeration of amylopectin and rearrangement of amylose, where it is verified that after the process less energy is needed to break the crystalline structure.…”
Section: Resultsmentioning
confidence: 91%
“…Although many studies have explored the effects of annealing on the structures, physicochemical properties, digestion, and gelatinization properties of starch, these investigations have primarily focused on the influence of different moisture content, temperature, or incubation time on one or more types of starch (Jeniffer, Barroso, Jam Pier, Delia Rita, & Raúl, 2021;Sun, et al, 2023;Zheng, et al, 2023). However, there is a notable absence of reports regarding the impacts of one-step and two-step annealing pretreatments on starch structural changes and oil absorption following frying.…”
Section: Introductionmentioning
confidence: 99%